Financial Market Spillovers in Transition Economies - Sahay, Ratna (IMF Working Papers; Working Paper, 2000)
This paper examines financial market comovements across European transition economies and compares their experience to that of their regions. Correlations in monthly indices of exchange market pressures can partly be explained by direct trade linkages, but not by measures of other fundamentals. Higher-frequency data during three crisis periods reveals the presence of structural breaks in the relationship between exchange-, but not stock markets. While the reaction of markets during the Asian and Czech crises is muted, the pattern of high-frequency spillovers during the Russian crisis looks very similar to that observed in other regions during turbulent times.